OPERATIONAL EXPERIENCE OF POLTAVA MUNICIPAL CLINICAL MATERNITY HOSPITAL IN IMPLEMENTATION OF ADVANCED TECHNOLOGIES - Удовицька, Н.О. (World of Medicine and Biology, 2015)
The paper presents comparative data for the year (2002 and 2012) the number of births, perinatal, early neonatal mortality, the number of affiliate birth and delivery complications in childbirth in the town of Poltava clinical maternity hospital with the introduction of innovative technologies.
Keywords: individual delivery rooms; affiliate birth; early breastfeeding